Validation Of The Multicultural Masculinity Ideology Scale In The Malaysian Context - Ying, Kelvin; Endut, Noraida; Mohd Hashim, Intan Hashimah; Selamat, Nor Hafizah; Azmawati, Azman Azwan (2016)
The Multicultural Masculinity Ideology Scale (MMIS) measures an individual’s perception of being a man, adapting in a specific cultural context. The MMIS was first introduced in a study by Doss and Hopkins (1998), where gender-specific masculinity ideology items were chosen based on theoretical grounds and constructed into a scale. The MMIS has been empirically examined and validated in different cultures (e.g., Anglo-American, African-American, Chilean, Russian and Korean cultures). The aim of this study is to explore the psychometric properties of the MMIS in the Malaysian context from the responses of 100 Malaysian male respondents in a public university. Psychometric properties were investigated using factor analysis, convergent validity tests, discriminant validity tests and internal consistency reliability assessment. Factor analysis by using varimax rotation discovered two cross-cultural components: Hypermasculine Posturing and Achievement. Internal consistency reliability was supported by high Cronbach’s alpha coefficients of the components and total scale. Evidence for discriminant validity was demonstrated through the relationship between the MMIS and the Bem Sex Roles Inventory (BSRI). Evidence for convergent validity was demonstrated by the relationship between the MMIS and the Gender Equity Men Scale (GEM). Findings validated MMIS in the Malaysian context. Implications for future research in the area of masculinity in Malaysia were discussed.